The Existence The Kitab Kuning Learning In Indonesian Boarding School - Intan Permata Sari; Fitria, Mita; Imron Rosyadi; Muhammad Irsan Barus; Novia Yanti (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
This study focuses on the instructional practices of Kitab Kuning (classical Islamic texts) teaching at Pondok Pesantren Arabi Darul Yamani, located in Sasak Ranah Pasisie, Pasaman Barat Regency. The aim of this research is to describe the planning, instructional process, and evaluation methods employed by teachers who are graduates of the pesantren system. Utilizing a descriptive method with a qualitative approach, data were collected through observations, interviews, and documentation. Data analysis was conducted through data reduction, data display, and drawing conclusions, while data validity was tested using triangulation. The findings reveal that in the planning phase, Kitab Kuning teachers who are graduates of the pesantren do not develop written learning objectives, curriculum mapping, or instructional tools such as lesson plans (RPP), syllabi, annual programs (Prota), or semester programs (Prosem). Instead, teachers rely on their understanding of the material and determine the extent of the syllabus coverage without systematic planning. In the instructional process, teachers conduct initial, core, and concluding activities with a considerable effort to achieve optimal results. Evaluation is carried out both in written and oral forms, at the end of the class sessions as well as after several meetings. These findings suggest that while the instructional and evaluative processes are generally well-implemented, there are notable shortcomings in the planning phase that could affect the overall effectiveness of the teaching and learning process.